Antibacterial Activity of Bacteriocin from Pediococcus pentosaceus Against Propionibacterium acnes: Molecular Docking, In Vitro, and 16S rRNA Genetic Identification - Adhitya Naufal Pribadhi; Penggalih Mahardika Herlambang; Ellyka Purwaningrum (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
This study aimed to evaluate the antibacterial potential of bacteriocin produced by lactic acid bacteria against Propionibacterium acnes through an integrative approach involving molecular docking, in vitro assays, and genetic identification using 16S rRNA sequencing. The target protein PDB 7LBU, representing the cell wall of P. acnes, was docked with Small Bacteriocin obtained from PubChem. The best binding affinity was recorded at –7.5 kcal/mol, indicating a stable interaction, supported by cavity analysis and ligand–protein interaction mapping using PyMOL. The results of the in vitro study, as determined by antibacterial activity testing against P. acnes, showed an average inhibition zone of 20.6 mm. In addition, genetic identification through BLAST confirmed the isolate as Pediococcus pentosaceus strain DSM 20336 with a similarity of 99.64%. These findings indicate that the bacteriocin derived from P. pentosaceus has promising potential as a natural agent in the development of alternative therapies for acne.